PENGARUH PERTUMBUHAN PENJUALAN, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) - Muhammad Adnan Ashari (2020)
This research is a quantitative study that aims to determine the effect of sales growth, institutional ownership and managerial ownership on tax avoidance. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the period of 2016-2018. This study uses 33 property and real estate companies listed on the Indonesia Stock Exchange in 2016-2018 as samples prepared based on purposive sampling techniques. Testing in this study uses Panel Data Regression Analysis techniques with the Stata program and a significance level of 5%. The results of the study obtained (1) there is no significant effect of sales growth on tax avoidance, (2) there is no significant effect of institutional ownership on tax avoidance, (3) the there is a positive and significant effect of managerial ownership on tax avoidance.